2005
DOI: 10.1002/ijc.21219
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous expression of GAGE, NY‐ESO‐1, MAGE‐A and SSX proteins in esophageal cancer: Implications for immunotherapy

Abstract: Cancer/testis antigens (CTAs) elicit immune response in cancer patients and are therefore targets of immunotherapy. Current information on CTA expression is primarily based on mRNA assays and little is known about their expression at the protein level. The objectives of our study are to analyze GAGE, NY-ESO-1, MAGE-A and SSX protein expression in esophageal cancer and to correlate their expression patterns with clinicopathologic parameters and survival. We examined CTA protein expression in 213 patients with e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
4

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 17 publications
3
33
4
Order By: Relevance
“…For this purpose, it is essential to determine the types of cancer that express CT antigens, at what frequency, and the pattern of expression within a given tumour, including percentage of positive cells, expression levels and the subcellular localization of expression. The expression of GAGE proteins in tumours has been addressed by RT -PCR in numerous studies, but until recently no anti-GAGE antibodies were available (Luftl et al, 2004;Akcakanat et al, 2006). In this study, we have generated a panel of GAGEreactive mAbs and used these to characterize the extent of heterogeneity in GAGE expression in malignancies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this purpose, it is essential to determine the types of cancer that express CT antigens, at what frequency, and the pattern of expression within a given tumour, including percentage of positive cells, expression levels and the subcellular localization of expression. The expression of GAGE proteins in tumours has been addressed by RT -PCR in numerous studies, but until recently no anti-GAGE antibodies were available (Luftl et al, 2004;Akcakanat et al, 2006). In this study, we have generated a panel of GAGEreactive mAbs and used these to characterize the extent of heterogeneity in GAGE expression in malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…This antibody, which recognized a 26-kDa band, similar to our anti-GAGE mAbs, was recommended only for Western blot applications by the manufacturer, but two recent studies have shown that this mAb is also suitable for immunohistochemical analysis (Luftl et al, 2004;Akcakanat et al, 2006). To compare the reactivity of this antibody with the reactivity of mAbs M2, M3 and M4, the anti-GAGE-7mAb was tested in parallel with M3 for reactivity with the panel of normal and cancer tissues by immunohistochemistry.…”
Section: Comparison Of the Reactivity Of The Anti-gage Mabs With Thatmentioning
confidence: 99%
“…Several studies have examined the expression of CT-X antigens in carcinomas of the digestive tract, either at the mRNA level by RT-PCR (23)(24)(25)(26) or, more recently, at the protein level by immunohistochemical (IHC) analysis (25,(27)(28)(29)(30). The latter is clearly more relevant clinically, either as a diagnostic marker or in predicting patients that might benefit from cancertestis antigen-based cancer vaccines, as posttranscriptional control of gene expression can lead to substantial discordance between mRNA and protein expression in cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…53,54 However, CGG expression is not correlated with disease progression in other malignancies such as neuroblastoma, 34-37 melanoma 55 and esophageal cancer. 56 We observed CGG expression in newly diagnosed tumors, in tumors collected after treatment with chemotherapy (osteosarcoma samples 5, 6 and 8 in Fig. 2) and in metastases.…”
mentioning
confidence: 69%